BPI-ANCA and Long-Term Prognosis among 46 Adult CF Patients: A Prospective 10-Year Follow-Up Study. (30th December 2012) - Lindberg, Ulrika; Carlsson, Malin; Löfdahl, Claes-Göran; Segelmark, Mårten
Abstract : Introduction . Anti-neutrophil cytoplasmic antibodies specific for bactericidal/permeability-increasing protein (BPI-ANCA) are frequent in CF patients and mainly develop in response to infection with Pseudomonas aeruginosa . It is not known to what extent BPI-ANCA correlates to prognosis. Objectives . To evaluate the prognostic value of IgA-BPI-ANCA, measured at the beginning of the study, for transplantation-free survival. Methods . A cohort of 46 adult, nontransplanted CF patients was generated, 1995–1998, and characterized using Leeds criteria, lung function, and IgA-BPI-ANCA levels measured by ELISA. The cohort was followed until December 2009, using the combined endpoint of death or lung transplantation. Results . Lung function and IgA-BPI-ANCA, but not Leeds criteria, were significantly associated with adverse outcome. No patient with normal lung function at baseline reached endpoint. Within 10 years 8/11 with high BPI-ANCA reached an endpoint compared to 3/17 ANCA-negative patients. A similar result was seen within the Leeds I group where 7 out of 9 BPI-ANCA-positive patients reached endpoint, compared to none of the 5 patients without BPI-ANCA. Conclusions . IgA-BPI-ANCA is associated with adverse outcome among Pseudomonas aeruginosa infected CF patients, suggesting that BPI-ANCA is a biomarker of an unfavourable host-pathogen interaction.